О легитимности использования формулы Стокса для доказательства теоремы Ампера (закон полного тока) - Кузьмин, Виктор Владимирович; Шпатенко, Виктор Сергеевич (НТУ "ХПИ", 2010)
В статье выполнен критический анализ современного подхода и предложен более простой и физически содержательный метод доказательства теоремы Ампера (закона полного тока).

On the buse of modern approach critical analysis the article demonstrate new, more simple and physically consistent method of Ampere’s theorem (Full Current Law) verification proof.
About legitimity of the use of formula Stocs for proof of Ampere's theorem (law of complete current)
Keywords: теорема Ампера; закон полного тока; формула Стокса; границы применимости ЗПТ; закон непрерывности; Ampere’s theorem; new method of proof